WHO HAS GOT WHAT?, WHY? AND HOW?: The Political Economy of Reintegration Policy in Aceh - Sait Abdullah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
This article focuses on the power relations between former GAM (Gerakan Aceh Merdeka) elite and non elite in the post conflict reintegration policy in Aceh. A number of scholars have linked the post conflict reintegration to the GAM ex-commanders conflicts over predatory processes of resource appropriation. However, what is missing in their account is that the attentions to the rank and file ex-fighters, including female ex-combatants. The finding of the study suggests that the post conflict reintegration has provided opportunities for the former GAM commanders to build and consolidate their political and economic power. Since the former GAM commanders occupied the reconstruction space, they have captured the peace building processes through their predatory behaviour and patrimonial networks. In this context, the ex- commanders GAM elite has become a new dominant post conflict group while the non-elite group of the rank and file ex-combatants, particularly women ex- combatants, lost opportunities to enhance their welfare. As local elites are powerful, they have the capacity to select who are excluded from and included in their alliances. In these circumstances, the welfare outcomes from post conflict reintegration will be framed in terms of 'who has got what?', 'why?',and 'how?'.